Presenting a Model of Social Accountability of Secondary School Authorities with an Emphasis on the Dimension of Biological and Physical Education: A Thematic Analysis Approach - Shafaei Tonekaboni, Sayed Ali; Pali, Samira; Sadoughi, Mitra (Assessment and Practice in Educational Sciences, 2025)
The purpose of this study was to present a model of social accountability of secondary school authorities with an emphasis on the dimension of biological and physical education. Based on data collection, this research is descriptive–analytical in nature, and regarding research orientation, it follows an inductive–deductive approach. Participants in the qualitative method of Braun and Clarke’s (2006) thematic analysis were 21 university experts, managers, and teachers from Mazandaran Province who had published relevant articles and possessed more than 10 years of experience in the field of social accountability in biological and physical education in schools. Sampling continued purposefully until theoretical saturation was reached with 19 participants. Initial interview questions were designed through a documentary study (books, articles, and related research). Before conducting each interview, the researcher first provided the interviewees with explanations regarding the subject and objectives of the study and then asked them to respond to the interview questions. It should be noted that the researcher, with due respect, requested that the interviewees themselves determine the appropriate time for the interviews so that they could respond in complete comfort. Furthermore, the researcher collected all interviews using both audio recording and note-taking. After preparing the written transcripts of the participants’ responses, the process of examining the explicit and implicit content of the collected data from statements and texts began. The aim of this process was to extract the components of the social accountability model of secondary school authorities with an emphasis on the dimension of biological and physical education, using the qualitative approach of thematic analysis. MAXQDA software was employed for analyzing the interview texts. From the analysis of 21 interviews, a total of 158 initial codes were extracted. Following the analysis, 56 selective codes and 10 sub-themes were identified. In the final stage, by reviewing the organizing themes, five overarching themes were obtained, namely: awareness and education; parental and community participation; resources and facilities; management and leadership; and the evaluation and supervision system.